Effect of Titania Nano-additives on Fine and Ultrafine Carbonaceous Emissions during Flame Combustion of Diesel - Akshat Jain; Anirudha Ambekar; Thaseem Thajudeen (Aerosol and Air Quality Research)
Abstract The severe impacts of emissions from combustion necessitate the need for advanced mitigation techniques. This study focuses on experimentally investigating the change in particulate matter (PM) emissions during the flame combustion of diesel blended with varying quantities of titania (TiO2) nano-additives. The initial observations using a Scanning Mobility Particle Sizer showed a reduction in the total number concentration (TNC) of PM emissions for TiO2-nanofuel samples compared to diesel. However, detailed investigations revealed the enhancement in the TNC of ultra-fine particles (UFPs) with mobility diameters less than 100 nm. This indicates the possibility of the emission of nano-additives during flame combustion, which enhances the number concentration of UFPs. The evolution of TiO2 nanoparticles is validated by performing the elemental composition analysis using energy-dispersive X-ray spectroscopy after sampling the PM emissions. A detailed experimental study also revealed the significance of the size and stability of the dispersed nanoparticles in the overall emissions. Ball milling (BM) was used for the size reduction of dispersed nanoparticles to enhance the dispersibility of the nano-additives. BM, when combined with bath-sonication (BS), resulted in the highest reduction in the TNC (37.70% for Ti100 BM-BS, 48.46% for Ti150 BM-BS, and 53.27% for Ti200 BM-BS), highlighting the importance of size of the dispersed nanoparticles. The detailed analysis of UFPs showed an increase in the TNC of particulates in sub-23 nm (22.92% for Ti100 BS and 39.16% for Ti100 BM) and super ultra-fine (96.46% for Ti100 BS, 100.83% for Ti100 BM, and 16.73% for Ti100 BM-BS) regions for nanofuel samples in contrast to neat diesel.